HUBUNGAN ANTARA KECERDASAN EMOSI DAN BUDAYA ORGANISASI DENGAN GAYA KEPEMIMPINAN SUPERVISI PRODUKSI DI PT. FABER CASTELL INDONESIA - Utami, Susiati Purwaning (Lembaga Layanan Pendidikan Tinggi Wilayah III Jakarta, 2014)
The success of a leader in managing an organization is influenced by a variety of factors including the ability of the individual as well as the organizational culture and the style of leadership. Emotional intelligence or emotional quotient (EQ) is the ability of a person to receive, assess, manage, and control the his emotions and others surrounding. Organizational culture is a value system that is believed to have been understood, applied and developed on an ongoing basis by all members in an organization. Leadership style is the behavior of an individual who led the activity – activity of a group to one goal to be achieved together. The purpose of disresearch is to determine: (1) the relationship between the emotional intelligence and leadership’style (2) the relationship between organizational culture and leadership’s style (3) the relationship between emotional intelligence and cultural organizations simultaneously with the leadership’s style. This research was conducted at PT.Faber Castell Indonesia with 157 people of production supervision employees as respondents taken by random. This quantitative research techniques data analysis used regression and correlation, the hypothesis test. The results showed that: (1) there is a positive andsignificant relationship between emotional intelligence and leadership (2) there is a significant and positive relationship between organizational culture and leadership’s style (3) there is a positive relationship between simultaneously emotional intelligence and Cultural Organization with the leadership’s style of production supervision at PT.Faber Castell Indonesia.